Cell competition during reprogramming gives rise to dominant clones - Shakiba, Nika; Fahmy, Ahmed; Jayakumaran, Gowtham; McGibbon, Sophie; David, Laurent; Trcka, Daniel; Elbaz, Judith; Puri, Mira C; Nagy, Andras; van der Kooy, Derek; Goyal, Sidhartha; Wrana, Jeffrey L; et al. (Science (American Association for the Advancement of Science), 2019)
The ability to generate induced pluripotent stem cells from differentiated cell types has enabled researchers to engineer cell states. Although studies have identified molecular networks that reprogram cells to pluripotency, the cellular dynamics of these processes remain poorly understood. Here, by combining cellular barcoding, mathematical modeling, and lineage tracing approaches, we demonstrate that reprogramming dynamics in heterogeneous populations are driven by dominant "elite" clones. Clones arise a priori from a population of poised mouse embryonic fibroblasts derived from Wnt1-expressing cells that may represent a neural crest-derived population. This work highlights the importance of cellular dynamics in fate programming outcomes and uncovers cell competition as a mechanism by which cells with eliteness emerge to occupy and dominate the reprogramming niche.